Stewardship Role Of Principals In Improving Teachers Professional Development in southern Districts Of Khyber Pakhtunkhwa - Jehanzeb Ullah; Zafar Khan; Allah Noor Khan (Elementary Education Online, 2023)
The present study focuses on the role of principals in improving Teachers’ Professional Development (TPD). The objectives of the study were to find out the role of principals as Steward in improving Teachers’ Professional Development (TPD).To compare the role of principals as Steward in improving TPD as perceived by Principals and Secondary School Teachers (SST). To compare the role of principals (Steward), in improving TPD in the perspective of southern districts of Khyber Pakhtunkhwa. The researcher adopted a quantitative research design for the study. The data was collected through a questionnaire. The population consists of principals/headmasters (413) and secondary school teachers (1523) working at the secondary school level. The current study took all the principals and teachers as the main population. A sample of 332(18%) participants of the whole population was selected through a stratified sampling method. There were 68 Principals and 264 SSTs. For data collection, a questionnaire was used. The result shows that the school principal has a significant role in improving the PD of teachers.They take part in teachers’ professional development with the help of training and classroom observations. They also motivate teachers to improve their professional skills.